Fiscal Implications of Interest Rate Normalization in the United States - Bi, Huixin (IMF Working Papers; Working Paper ;, 2019)
This paper studies the main channels through which interest rate normalization has fiscal implications in the United States. While unexpected inflation reduces the real value of government liabilities, a rising policy rate increases government financing needs because of higher interest payments and lower real bond prices. After an initial decline, the real government debt burden rises even with higher tax revenues in an expansion. Given the current net debt-to-GDP ratio at around 80 percent, interest rate normalization leads to a negligible increase in the sovereign default risk of the U.S. federal government, despite a much higher federal debt-to-GDP ratio than the post-war historical average.